Between Tradition and Modernity: Dynamics of Krobo Marriage Rites in the Eastern Region of Ghana - Abbey, Elizabeth Anorkor; Nasidi, Nadir A. (UIN Sunan Gunung Djati Bandung, 2024)
Purpose of the Study: This research delves into the dynamic evolution of marriage rites within the Krobo community in Eastern Ghana, focusing on the 'la-pomi' and 'fia' ceremonies. Methodology: Employing a qualitative approach, the study utilized narrative analysis to capture the intricate perspectives surrounding the 'la-pomi' and 'fia' marriage rites. Twenty-four participants from Krobo-Odumase and its environs, aged between 20 to 60 years, were purposively sampled and interviewed in two phases. Main Findings: The study unveiled a significant transformation in the Krobo marriage rites, from highly structured ceremonies to more adaptable forms blending traditional elements with modern practices. Key factors driving this evolution include urbanization, the influence of Western education, and the interplay with legal frameworks, all contributing to the rites' ongoing adaptation. Despite these changes, a strong commitment to preserving cultural identity remains evident among the Krobo people, showcasing their resilience and innovative approaches to sustaining cultural traditions. Applications of this Study: By highlighting the adaptive strategies employed by the Krobo community, this research contributes to broader discussions on cultural sustainability, identity, and social cohesion in the face of global changes. Novelty/Originality: This research underscores the complex negotiation process between preserving cultural heritage and embracing change, offering a unique perspective on the resilience and dynamism of Krobo cultural practices in a rapidly changing world.